Consumer Perceptions About Online Service Quality: Persepsi Konsumen Tentang Kualitas Layanan Online - Putri, Lusiana Indah Setyo; Sinduwiatmo, Kukuh (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine how consumers perceive the quality of service provided by CV Momentum Bertumbuh Indonesia as a company engaged in online guidance services. For a company to pay attention to the quality of good service to consumers is important so that consumers feel satisfied, have a good perception and foster loyalty. The research uses a qualitative method with a case study approach. Collecting data through interviews, observations and documentation with purposive sampling informant determination technique. Indicators to measure service quality are tangible, reliability, responsiveness, assurance, and empathy. The results of this study indicate that the company has a positive perception because it provides facilities according to what consumers expect and is responsive to providing services according to company procedures. There is a guaranteed fee provided and the mentoring process runs smoothly. However, there is a negative perception because some customer service in providing services is not timely and the company needs to provide facilities that can be accessed offline